Factors Related To The Level Of Knowledge On Clean Living Behaviorand Healthy (Phbs) In Banda Aceh Primary Students - Aulia zulkifli, Riski; Meutia Zahara; Riza Septiani (JURNAL KESMAS DAN GIZI (JKG), 2024)
Clean and healthy living behavior is the essence for the sustainability of the program launched by the government as an indicator of sustainable health improvement achievements. The realization of PHBS in school settings needs to be pursued, to increase self-awareness of the results of the target, namely students and school residents and supported by the existence of facilities and infrastructure. This study aims to determine the factors related to the level of knowledge of clean and healthy living behavior (PHBS) in students of SD N 58 Alue Naga Banda Aceh. The type of research used is quantitative with a cross-sectional research design, namely research that studies the correlation between exposure or independent risk factors (level of knowledge, sex, attitude, personal hygiene, and incidence of diarrhea) with dependent effects or effects (PHBS). The sampling technique used was total sampling and obtained 82 students of grades V, and VI.. Data analysis is univariate and bivariate. Based on the analysis using coputerization with the chi-squre test, it was found that there was a significant relationship between the level of knowledge (p-value 0.027), gender (p-value 0.017), attitude (p-value 0.040), personal hygiene (p-value 0.027) and history of diarrhea (p-value 0.018) on clean and healthy living behavior (PHBS) in students of SDN 58 Alue Naga Banda Aceh. The conclusion of the results of this study is that there is a significant relationship between the level of knowledge, gender, attitude, personal hygiene, and the incidence of diarrhea on PHBS students of SD N 58 Alue Naga Banda Aceh.